A theory-informed, experiment-based constraint on the rate of autoxidation chemistry – an analytical approach - L. Pichelstorfer; L. Pichelstorfer; S. P. O'Meara; S. P. O'Meara; G. McFiggans (Aerosol Research, 2025)
Autoxidation is a key process that transforms volatile organic compounds into condensable species, thereby significantly contributing to the formation and growth of airborne particles. Given the enormous complexity of this chemistry, explicit reaction mechanisms describing autoxidation of the multitude of atmospherically relevant precursors may appear out of reach.